The Mediating Role of Learning Orientation on the Effect of Customer and Competitor Orientation on MSME Business Performance - Rusmawati, Zeni; Oktaviani, Marista; Solehah, Alfia Rohmatus (Universitas Muhammadiyah Sorong, 2025)
The purpose of this study was to determine the effect of competitor orientation and customer orientation on business performance mediated by learning orientation. Learning orientation is taken as a mediating variable, because MSMEs must continue to learn and learn, so that they are able to have a competitive advantage. Muhammadiyah's role in supporting this is through the LAZISMU institution, namely through the MSME empowerment program. The MSME empowerment program, in addition to distributing funds, also provides coaching and learning for MSME actors so that they can run their businesses well. This study uses a quantitative approach, by distributing research questionnaires to MSME actors fostered by LAZISMU. There are 53 respondent data processed using SmartPLS. This study uses PLS-SEM analysis with the results of the direct influence between customer orientation on learning orientation and business performance showing positive and significant results, as well as the influence of competitor orientation on business performance. However, competitor orientation on customer orientation does not show a direct influence. The results of the mediation test, the influence of customer and competitor orientation on business performance can be mediated by learning orientation. This shows that learning orientation improves the organization's ability to translate market insights into strategies and innovations that improve business performance. In other words, only MSMEs that are able to internalize customer information and use it as a basis for continuous learning will be able to consistently create business value.